Relação da temperatura e da umidade relativa com internações e mortes por doenças cardiovasculares, respiratórias e distúrbios mentais - Silva, Iara da (2020)
The changes in the Paraná climate, with a gradual increase in temperatures and changes in the relative humidity, and also taking into account the aging population, may represent problems for public health, given that future scenarios predict even more marked changes in meteorological variables and age pyramid. Thus, this study aimed to evaluate the effects of maximum and, minimum temperatures and, relative humidity on hospitalizations and deaths from cardiovascular, respiratory and mental diseases in adults and the elderly, of both sexes, in the Paraná state. Statistical analyzes were performed on time series (1996-2015) of public health and meteorological data in the public domain from 16 metropolitan regions (representing 84% of the area and 85% of the population). Health data were stratified into six groups, according to sex and an age range for each region. For the investigation of the series temporal characteristics, it was applied Mann-Kendall test in conjunction with bootstrap and a transformed Morlet wavelet, for hospitalizations and deaths. For regression analysis, two distributions (Poisson and binomial negative) were tested, with and without zeros adjustment, by considering the excess or not, for a complete series and percentiles. Finally, the related risks (RR) were calculated and the effects were evaluated up to seven days after the occurrence. The results showed a tendency to reduce the prevalence of cardiovascular, respiratory and mental diseases, but it increases, in the most regions the number of the deaths due to respiratory causes. The negative binomial distribution better fitted the data and the lag 0 was the most significant, but with other lags also significant to some groups and diseases. High temperatures, in conjunction with low temperatures, were the most relevant risk factors for hospitalizations for cardiovascular diseases, while minimum temperatures were the most relevant factor for respiratory diseases. Temperature extremes, both high and low, were the most important risks factors for mental illnesses. Groups over 60 years presented higher risks for cardiovascular and respiratory diseases, while for mental disease, the higher risk was for the adult group (40-59 years). In general, was not found differences between men and women and, when comparing the regions, those with higher urbanization levels were the ones that presented the biggest risks, mainly for respiratory diseases, while those with lower urbanization levels were the ones that stood out for cardiovascular diseases.